Usos do hiper-realismo sonoro no cinema brasileiro de ficção contemporâneo : análises de O Som ao Redor (2012) e Mar Negro (2013) - Ferraço, Felipe Mattar (2016)
This work presents the study about the influences of the sound hyperrealism in the contemporary Brazilian cinema. For this, it sought to study the relations between the men and the sound in the quotidian along the sound experience in cinema. Identify how,